Fatores associados à síndrome de burnout em profissionais da atenção primária durante a pandemia de COVID-19 - Marques, Mariane da Rocha (2021)
Introduction:Primary Care (PC) professionals are subject to psychosocial risks that contribute to physical and mental illness. With the pandemic, the overload in the care of patients with COVID-19, professionals have become the second victim of the phenomenon. They suffer great psychological pressure in carrying out their activities, which impacts on the emergence of work stress, in addition to burnout syndrome, insomnia, depression, anxiety, anguish and distress. Objectives:To evaluate the factors associated with the presence of signs of Burnout Syndrome in professionals working in Primary Care during the COVID-19 pandemic. Methods:Observational, cross-sectional study with a quantitative approach carried out with professionals working in PC during the COVID-19 pandemic. This is a non-probabilistic convenience sample composed of 160 professionals. Data collection was carried out in a virtual way, using the GoogleForms platform. Three instruments were used: Characterization Questionnaire, Maslach Burnout Inventory (MBI) and Perceived Stress Scale-14 (PSS-14). The description of the factors of interest performed by descriptive analysis of numerical and categorical variables. Pearson's chi-square test by contingency table was applied to analyze the relationship of the outcome (Burnout syndrome) with the independent variables of gender, professional category and presence of stress. A multivariate model was developed with variables previously associated with the outcome ( bivariate analysis).Results: 57.5% of professionals showed Burnout. 53.1% of Primary Care professionals reported self-perception of stress, which increased the chance of the outcome by thirteen times. 78.3% of professionals with the syndrome reported overload with the pandemic and dissatisfaction with the service increased the chance of the outcome by more than six times. 85.3% of professionals who did not develop Burnout Syndrome (BS) reported receiving emotional support from their immediate superiors. Lifestyle, working hours, remuneration and virus infection were relevant for BS. Conclusion:The factors associated with BS are aspects related to work, the pandemic and stress. The crucial and urgent importance of raising discussions about the inestimable value of investing in workers' mental health actions is highlighted.